Modeling structural deformation and failure in fluid-structure interaction with WC-TLSPH - Wu, Haitao; Gu, Shenglong; Tian, Lirong; Li, Jiaye; Chen, Chen; Zhang, Chi (Frontiers in Environmental Science, 2022)
In this paper, the coupled weakly compressible (WC) and total Lagrangian (TL) smoothed particle hydrodynamics (SPH) model based on the open-source multi-physics and multi-resolution SPHinXsys library is used to simulate the structural deformation and failure problem in fluid-structure interaction (FSI). Aiming at the problem that the original TLSPH method could not simulate the cracks and their propagation, the fracture model based on TLSPH is established, and then verified by fast-loading and slow-loading cases respectively. With the fracture model in hand, the TLSPH method is coupled with the WCSPH method to simulate the breaking dam flow impacting on an elastic/elastoplastic baffle. The comparison with the literature data shows that the present coupled WC-TLSPH model can accurately simulate the FSI problem where figurative fracture process is involved, indicating the compromising potential of the established model to simulate the elastoplastic structural failure in scientific and industrial applications.